Cationization of catalase, peroxidase, and superoxide dismutase. Effect of improved intraarticular retention on experimental arthritis in mice. - Schalkwijk, J (1985)
Several enzymes and other proteins were made cationic either by coupling to polylysine or by shielding of anionic sites. These cationic proteins, all having an isoelectric point greater than 8.5 exhibited excellent retention in articular structures when injected in mouse knee joints. Autoradiography and histochemistry showed that cationic forms of catalase, superoxide dismutase, and horseradish peroxidase were firmly retained by synovial and cartilaginous tissues. The half-life of these enzymes in the joint is thus significantly extended compared with native enzymes. The native enzymes and their cationic derivatives were tested for antiinflammatory properties in mice, using antigen-induced arthritis and zymosan-induced arthritis. It was found that injection of cationic catalase or peroxidase induced a marked suppression of some parameters of the inflammatory response in both types of arthritis, as measured by 99m technetium pertechnetate uptake and leakage of 125I-labeled albumin. Native catalase and peroxidase were less, or not at all effective. Cationic superoxide dismutase or cationic nonenzyme proteins did not suppress inflammation. The observed suppression of two different types of inflammation (an immune and a nonimmune arthritis) by catalase and peroxidase suggests that elimination of peroxides contributes to the suppression of an inflammatory response. We would hypothesize that cationic enzymes offer the possibility for investigating the mechanisms of inflammation and, in addition, might be interesting from a therapeutical point of view.